SIMULASI PERBANDINGAN PERUBAHAN TILT TERHADAP ENERGI ARRAY PADA 34 UNIT PLTS ROOFTOP 100 KWP DI INDONESIA - Hero Gunawan; Budi Sudiarto (DAS Institute, 2022)
One of the activities to developing the use of rooftop solar panels in Indonesia in accordance with the mandate of RUEN is the mandatory use of solar cells at a minimum of 30% of the roof area for all government buildings. In this regard, good planning related to engineering is needed, one of which is the orientation and tilt aspects used. In International, to assist countries in achieving sustainable development goals for new and renewable energy, the World Bank Group partnered with Solargis, releasing a web-based application called Global Solar Atlas (GSA) with optimum tilt and energy arrays as research references. From this study, it was found that tilt changes greatly affect the resulting array energy, an average change of 10 from 00-160 can result in changes in addition of up to 578 kWh and reduction of up to 483 kWh. The largest array energy potential value is located in the province of Bali at 16.5872 kWh and the smallest in West Kalimantan at 12.1924 kWh., while compared to the modeling in the GSA application, the largest array energy value is in NTT with a value of 16.5673 kWh and the smallest is in East Kalimantan with rated 12.1843 kWh. The tilt value in Indonesia from 34 simulated locations is at 00-130 and is still in the tilt range in Indonesia according to the GSA application, which is 00-140.